Probabilistic evaluation and planning of power transmission system reliability. Issue 5 (23rd January 2017) - Makvand, Saeid Biglary; Venkatesh, Bala; Cheng, Daniel; Yu, Peng
Abstract : Modern power systems are designed prudently and then operated according to the permitted equipment limits set out in standards, policies, and procedures. To meet the growing demand, utilities apply transmission expansion tools for planning and updating their transmission assets. However, due to their unpredictable nature, transmission contingencies cannot be easily integrated during the planning stage. Although computationally cumbersome, probabilistic planning is an approach that could enable an objective comparison of the economic risk associated with a contingency event versus the cost of upgrades. In the context of the development of a generic assessment tool for such a process that could be employed by utilities, this study presents a systematic approach for transmission system expansion planning that includes consideration of an N − 1 contingency. The proposed method provides an estimate of the potential economic losses that could occur due to contingencies related to transmission, which are quantified as the cost of expected energy not supplied. The study then introduces a proposed formulation that computes an optimal plan for transmission system reinforcement that will eliminate the economic losses associated with N − 1 contingencies. The results reveal that in specific cases, upgrading the system has economic merit as well as offering the benefits to be derived from a robust transmission system.